1978
DOI: 10.1007/bf01871998
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic study of gill epithelium permeability to water diffusion in the fresh water trout,Salmo gairdneri: Effect of adrenaline

Abstract: Summary. Using isolated head perfnsed at constant flow rates, close to those occurring in vivo, the movement of tritiated water through the gill epithelium of the trout, Salmo gairdneri was studied.The analysis of the curves of loading and unloading of tritiated water between the gill epithelium and the external and internal media shows two exponentials with different slopes in each medium. As the rapid exponentials have identical slopes, the external medium, the gill epithelium, and the perfusion medium const… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1979
1979
1995
1995

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(5 citation statements)
references
References 25 publications
(27 reference statements)
1
4
0
Order By: Relevance
“…This suggests that the limiting factor for diffusion of non-electrolytes is probably the apical and basal membranes and not the tight intercellar junctions. Such evidence is in accord with the results of Isaia et al (1978b) for water permeability, and it seems logical to assume this for the other molecules whose molecular diameters exceed the ionic radius of the impermeant lanthanum ion.…”
Section: Hydrophilic Characteristics Of the Respiratory Cells (Secondsupporting
confidence: 85%
“…This suggests that the limiting factor for diffusion of non-electrolytes is probably the apical and basal membranes and not the tight intercellar junctions. Such evidence is in accord with the results of Isaia et al (1978b) for water permeability, and it seems logical to assume this for the other molecules whose molecular diameters exceed the ionic radius of the impermeant lanthanum ion.…”
Section: Hydrophilic Characteristics Of the Respiratory Cells (Secondsupporting
confidence: 85%
“…Short term changes in gill permeability may be attributed to an increase in circulating catecholamines. Epinephrine greatly increases the permeability of the gill to small hydrophilic molecules, including water and urea (Isaia et al 1978).…”
Section: Discussionmentioning
confidence: 99%
“…Stress-mediated release of epinephrine may be the key element in compensating for loss of surf ace area. Isaia, Girard & Payan (1978a), Isaia,Maetz& Haywood (1978b) and Isaia (1979) have shown that epinephrine increases branchial permeability to the lipophilic substance butanol and to water and urea. Isaia etal.…”
Section: Qualitative Studies: Pathogenesis Of Branchial Lesionsmentioning
confidence: 97%